Identification of risk areas as a method of surveillance of dengue cases - Lopes, Gesiel Rios; Pelarigo, Karina Jorge; Delbem, Alexandre C. B. (Anais da Escola Regional de Computação do Ceará, Maranhão e Piauí (ERCEMAPI); 2022: Anais da X Escola Regional de Computação do Ceará, Maranhão e PiauíDO - 10.5753/ercemapi.2022.225892, 2022)
Identifying spatial clusters of risk for dengue cases according to social vulnerability constitutes a powerful tool for effective epidemiological and urban management. In this way, this work carries out an ecological study that considered confirmed cases of dengue and actions of endemic agents in the municipality of São Carlos-SP, in the year 2019, through the application of the spatial scan technique for classification of the risk areas, computing the relative risk (RR), with a confidence interval of 95% (CI95%:) and the São Paulo Social Vulnerability Index (IPVS) to characterize these areas. Seven clusters were identified, two of which were high risk (RR=37.54 / RR=33.39), with the highest risk located in a region with high vulnerability and the second in a region with very low vulnerability. These results provide information that allows the targeting of specific control actions from the early detection of cases in places with greater dengue transmissibility.